BINARY OPOSITION IN SARANTUANG BARALIENG KUNYAIT FOLKTALE SITINJAU LAUT KERINCI - Jayawardana, Mahawitra; Anwar, Khairil (Universitas Andalas, 2020)
This study discusses the binary opposition in oral stories of Sarantuang Baraliang Kunyait, which is located in Sitinjau Laut District, Kerinci Regency. Oral literature is in the form of a fairy tale which is still developing in society even though the media has changed, from word of mouth to mouth, now in digital form. This fairy tale tells the story of miscommunication between grandchildren and grandmothers, resulting in tragedy at the end of the story. This fairy tale has a message human and cultural values. To get that value, it is necessary to read it with kualitative methode and out using a deconstruction theory analysis knife. From this study it is found that, these tales have signs of binary opposition, parallelism, and hierarchical reversals.